2018
DOI: 10.1186/s12885-018-5170-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of S100 family members in ovarian cancer patients

Abstract: ObjectiveExhibiting high consistence in sequence and structure, S100 family members are interchangeable in function and they show a wide spectrum of biological processes, including proliferation, apoptosis, migration, inflammation and differentiation and the like. While the prognostic value of each individual S100 in ovarian cancer is still elusive. In current study, we investigated the prognostic value of S100 family members in the ovarian cancer.MethodsWe used the Kaplan Meier plotter (KM plotter) database, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 83 publications
1
47
0
1
Order By: Relevance
“…Higher tissue expression of S100A2 was significantly correlated with worse overall survival in ovarian cancer patients [15], and S100A2 protein expression in saliva was observed to be higher in oral squamous cell carcinoma patients in comparison to other oral potentially malignant disorders. S100A6 expression has been associated with worse prognosis or the progression of several cancers including oncogynecology [50], colorectal [51], gastric [52], and renal [53]. In contrast, a recent study suggests a relation between S100A6 expression and better prognosis in breast cancer [54].…”
Section: Discussionmentioning
confidence: 99%
“…Higher tissue expression of S100A2 was significantly correlated with worse overall survival in ovarian cancer patients [15], and S100A2 protein expression in saliva was observed to be higher in oral squamous cell carcinoma patients in comparison to other oral potentially malignant disorders. S100A6 expression has been associated with worse prognosis or the progression of several cancers including oncogynecology [50], colorectal [51], gastric [52], and renal [53]. In contrast, a recent study suggests a relation between S100A6 expression and better prognosis in breast cancer [54].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigating mRNA expression of S100 proteins in correlation with the survival of ovarian cancer patients demonstrated that high levels of the S100 family members S100A2, S100A10, S100A11, S100A15, S100A16, and S100B predict worse OS, while S100A1, S100A3, S100A5, S100A6, S100A13, S100G, and S100Z are associated with longer OS, partially depending on cancer subtype and clinicopathological features [144,145]. However, the underlying mechanisms of these S100 proteins in the context of ovarian cancer have not yet been fully understood.…”
Section: S100 Proteins In Ovarian Cancermentioning
confidence: 99%
“…Armed with functionalities such as differential expression analysis, survival analysis, and similar gene identification, GEPIA provided experimental biologists and clinicians with a handy tool to explore TCGA and GTEx datasets. GEPIA has aided the investigation of various genes in multiple cancer types (5,6), and led to the identification of potential biomarkers (7) and therapeutic targets (8,9).…”
Section: Introductionmentioning
confidence: 99%